The exploitation of trypanotolerance: A dream of academics or a reality for sustainable livestock Development in tsetse affected areas? - D'Ieteren, G.D.M. (OAU/STRC, 2001)
Trypanotolerance is one of the best recognised examples of innate resistance to disease and one of the most thoroughly investigated. Experimental and field studies Reported in this paper are providing the basic tools with which the trypanotolerance trait can be identified and exploited. Evaluation of the degree of genetic determination of the different disease resistance traits, their heritability and their genetic correlations with each other and with animal performance traits should now be possible; this knowledge will allow progress to be made in the Development of breeding programmes and policies. There is increasing recognition that Africa possesses animal genetic resources probably unparalleled in any other continent. Evidence that these resources can provide sustainable and environmentally sound solutions for some of the vast disease problems currently confronting Africa is now being found. Thus, the natural innate resistance possessed by breeds of cattle, such as the N'Dama and the West African shorthorn, to trypanosomosis and to several other important infectious diseases is now accepted as an important component of national and regional disease control programmes. The fact that these breeds also possess considerable production potential and that their disease resistance traits could be exploited in crossbreeding offers an unparalleled opportunity to improve livestock production in the vast areas of Africa dominated by the tsetse fly, ticks and helminths, particularly as production systems evolve into more market-orientated production.